Bahasa Propaganda Baliho Partai Politik Nasionalis Pemilu 2019: Analisis Semiotika Sosial - G. Putu Satya Amarta Dewi (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2021)
This study aims to deepen the understanding of using propaganda language in political campaign billboards advertisements. Data sources include billboards from 2 Nationalist parties in the 2019 general election, namely PDI-P and NasDem. The research data consisted of visual text and written text contained on billboards. This study uses a qualitative approach with an interpretive type to analyze written and visual texts on billboards. The study results, namely the two billboards that have been analyzed show similarities in the mechanism of the propaganda language applied to the object of the billboards participants, including logos, slogans, supporting figures, background color and the color of the candidate's clothes. In conclusion, the object of the billboard participant contains propaganda meaning to attract the attention of the public as well as the mechanism of the moving billboard propaganda language through logos, slogans, photo techniques, color composition, image arrangement, supporting figure figures, background color and color of candidate clothes. Keywords: Propaganda Language, Billboards, Multimodal, Nationalist Political Parties, Social Semiotics